Critical Reflection: A Textbook for Critical Thinking - Murray, Malcolm; Kujundzic, Nebojsa (MQUP, 2005)
In an era of information overload, our need to learn how to critically evaluate the growing flood of information has never been greater. Critical Reflection showcases the role of reason in a world saturated by media-enhanced persuasion and complex scientific and technological jargon. Drawing from the classic philosophical texts, this engaging textbook on the art of analyzing arguments is also relevant to today's undergraduates in its use of real-life examples and exercises drawn mainly from media and politics. Malcolm Murray and Nebojsa Kujundzic cover the standard subjects in a one-semester course on critical thinking, offering ways to analyze arguments in the following areas: * language use * acceptability conditions for truth * categorical and propositional logic * induction * causal claims * probability reasoning * analogical reasoning * an in-depth analysis of informal fallacies Critical Reflection further distinguishes itself with in-depth answers to chapter exercises that are incorporated directly into the authors' detailed discussions. This is an ideal textbook to help professors foster autonomous thinking among their students.